Effects of the gel size before ingestion and agarose molecular weight on the textural properties of a gel bolus. (April 2019) - Moritaka, Hatsue; Yamanaka, Kentaro; Kobayashi, Naoki; Ishihara, Miki; Nishinari, Katsuyoshi
Abstract: The purpose of this study was to obtain basic information on the factors that affect bolus formation. We investigated the effects of the gel size before ingestion and agarose molecular weight on the instrumental textural properties and particle size distribution of boluses collected after different oral processing durations. Six types of agarose gel samples with three different molecular weights and two sizes (one 15 mm × 15 mm × 15 mm cubic particle and the 3 mm × 3 mm × 3 mm cubic particles with the same total volume as that of the 15 mm × 15 mm × 15 mm gel) were examined. A mouthful was used as the bolus volume for each measurement. The textural properties of the gel bolus were found to be influenced by not only the molecular weight of the agarose composing the gel but also the gel size before ingestion. In the early stages of chewing, the initial bolus hardness and rate of hardness reduction were strongly influenced by the molecular weight of the agarose and the gel size before ingestion with the influence decreasing in the later stages of chewing. In the middle and late stages of chewing, the adhesiveness, cohesiveness, and the rates of increase in adhesiveness or cohesiveness were affected by the molecular weight of agarose; however, these properties were not affected by the gel size before ingestion throughout the chewing process. The average particle size showed a high correlation with the hardness but low correlations with the adhesiveness and cohesiveness. Graphical abstract: Highlights: Texture characteristics of mouthful volume of bolus were influenced by the agarose molecular weight. Hardness reduction rate of bolus was larger in one 15-mm particle than in the 3-mm particles. Small particles of masticated 15-mm gel of all types fitted the log-normal distribution.